2019
DOI: 10.31289/biolink.v6i1.2210
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktivitas Antibakteri Ekstrak Daun Serai Wangi (Cymbopogon Nardus) Terhadap Bakteri Propionibacterium Acnes

Abstract: Acne is a disease of the skin that often occurs during adolescence until adulthood. Acne is characterized by the appearance of several signs, namely blackheads, pustules, papules, cysts and nodes in the neck, face, upper arms, back and chest area. Acne is also a skin disease that affects more than 85% of adolescents around the world. Although not life-threatening, acne can affect a person's quality of life by giving a psychological effect that is bad for the sufferer in the form of a person's way of judging, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Weighed as much as 1.7 g of NA media powder, then put into an erlenmeyer and added 60 ml of distilled water, then heated on a magnetic stirrer while stirring until the NA medium dissolved completely. The NA media solution was covered with aluminum foil and sterilized in an autoclave for 15 min at 121 °C [7].…”
Section: E Media Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Weighed as much as 1.7 g of NA media powder, then put into an erlenmeyer and added 60 ml of distilled water, then heated on a magnetic stirrer while stirring until the NA medium dissolved completely. The NA media solution was covered with aluminum foil and sterilized in an autoclave for 15 min at 121 °C [7].…”
Section: E Media Preparationmentioning
confidence: 99%
“…According to previous research conducted by Fitria and Febrianti (2020) [6], showed that 70% ethanol extract of fragrant lemongrass leaves had antibacterial activity against Staphylococcus aureus bacteria. The results of research by Winato et al (2019) [7], stated that 96% ethanol extract of fragrant lemongrass leaves had an inhibitory effect on the growth of Propionibacterium acnes which causes acne. Another study by Mayasari and Sapitri (2019) [8] found that at concentrations of 20%, 30%, 40% and 50% lemongrass leaf juice was able to inhibit Streptococcus mutans bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Teknik sampling adalah merupakan teknik pengambilan sampel untuk menentukan sampel yang akan digunakan dalam penelitian (Winato, 2013). Dalam pei nei lii tii an ii nii , tei knii k samplii ng yang dii gunakan adalah purposii vei samplii ng.…”
Section: Metode Penelitianunclassified
“…Citronella oil showed an inhibitory effect on the growth of gram-negative and gram-positive bacteria (Wei & Wee, 2013). Another study stated that citronella inhibits the activity of the bacteria Propionibacterium acnes (Winato et al, 2019), and citronella leaves could inhibit the activity of Staphylococcus aureus bacteria (Yuliyani & Sidharta, 2010) The stability and physical properties of the gel depends on the gelling agent used. In the formulation of gel preparations, optimisation of the gelling agent is needed to find a physically stable gelling agent that follows applicable standards (Aponno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%